The Influence of MMP-3 towards MMP-9 among Emphysematous Patients from Gingival Crevicular Fluid and Sputum - Mulkan Azhary; Muhammad Amin; Soetjipto Soetjipto; Mulyadi Mulyadi; Sunnati Sunnati (Syiah Kuala University, 2015)
The elevated activity of matrix metalloproteinase (MMP)-9 has been responsible for degradation of extracellular matrix (ECM) within lung parenchyma leading to emphysema among patientssuffering from chronic obstructive pulmonary disease (COPD). Prolonged exposure of smokinghad triggered activation of both MMP-9 and MMP-3. Active MMP-3 might degrade numerous kinds of ECM and act as MMP-9 inducer as well. The study aimed to correlate active MMP-3 towards elevated MMP-9 activity from both gingival crevicular fluid (GCF) and sputum to assess breakage of extracellular matrix (ECM) among emphysematous patients. Fifteen emphysematous respondents suffering from COPD were recruited to undergo thoroughly physical assessment, spirometry, and radiological examination. Then, both GCF and sputum were collected for measurement of MMP-3 and MMP-9 activity. Results showed that MMP-3 activities were correlated positively and significant with elevated MMP-9 activities from both GCF and sputum i.e. r = 0.899 (p0.05) and r = 0.770 (p0.05) respectively. Smoking exposure released many radicals and oxidants generating elevation of MMP-3 activity which then influenced repeatedly influx of neutrophils and activation of MMP-9. The role of active MMP-3 also involved in either acute inflammatory or broad ECM breakage. Moreover, active MMP-9 might lead mainly the degradation of ECM within lung parenchyma. Because of similar effect and impact concerning ECM degradation, both active MMP-3 and MMP-9 might concurrently cause larger breakage of ECM leading to lung emphysema among COPD patients. This study showed that both GCF and sputum would be assigned to evaluate active MMP-3 and MMP-9 for assessing ECM degradation among emphysematous patients.